De novo variants in CDKL1 and CDKL2 are associated with neurodevelopmental symptoms. - Bereshneh, A.H.; Andrews, J.C.; Eberl, D.F.; Bademci, G.; Borja, N.A.; Bivona, S.; Undiagnosed Diseases Network; Baylor College of Medicine Center for Precision Medicine Models; Chung, W.K.; Yamamoto, S.; Wangler, M.F.; McKee, S.; et al. (American Journal of Human Genetics, 2025)
The CDKL (cyclin-dependent kinase-like) family consists of five members in humans, CDKL1-5, that encode serine-threonine kinases. The only member that has been associated with a Mendelian disorder is CDKL5, and variants in CDKL5 cause developmental and epileptic encephalopathy type 2 (DEE2). Here, we study four de novo variants in CDKL2 identified in five individuals, including three unrelated probands and monozygotic twins. These individuals present with overlapping symptoms, including global developmental delay, intellectual disability, childhood-onset epilepsy, dyspraxia, and speech deficits. We also identified two individuals with de novo missense variants in CDKL1 in the published Deciphering Developmental Disorders (DDD) and GeneDx cohorts with developmental disorders. Drosophila has a single ortholog of CDKL1-5, CG7236 (Cdkl). Cdkl is expressed in sensory neurons that project to specific regions of the brain that control sensory inputs. Cdkl loss causes semi-lethality, climbing defects, heat-induced seizures, hearing loss, and reduced lifespan. These phenotypes can be rescued by expression of the human reference CDKL1, CDKL2, or CDKL5, showing that the functions of these genes are conserved. In contrast, the CDKL1 and CDKL2 variants do not fully rescue the observed phenotypes, and overexpression of the variant proteins leads to phenotypes that are similar to Cdkl loss. Co-expression of CDKL1 or CDKL2 variants with CDKL1, CDKL2, or CDKL5 references in the mutant background suppresses the rescue ability of the reference genes. Our results suggest that the variants act as dominant negative alleles and are causative of neurological symptoms in these individuals.